(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
The present study explores the angiosperm flora belonging to the class Liliopsida in Rajbari district, seamlessly integrating taxonomy with phytocompound-based drug discovery through advanced computational biology approaches. The study covered all five upazilas (sub-districts) of the district. A total of 201 taxa across 118 genera and 24 families of Liliopsida were identified. The flora is predominantly composed of herbs (79.06%), followed by climbers (7.96%), trees (7.46%), shrubs (2.98%), and a minimal occurrence of epiphytes (1.99%). Poaceae emerged as the largest family, comprising 58 taxa across 36 genera, followed by Araceae (26 taxa) and Cyperaceae (17 taxa). Notably, the study identified 25 medicinal plant species under Liliopsida. Some rare species within Liliopsida, such as Coix aquatica, Wolffia arrhiza, Typha domingensis, and Schumannianthus benthamianus were also recorded in the study area. Among the medicinal plants identified, Amorphophallus paeoniifolius (Dennst.) Nicolson was selected for further investigation into colorectal cancer drug discovery. The computational therapeutics design endeavor unveiled two lead compounds: Riboflavin (-7.9 kcal/mol) and Lupeol (-6.1 kcal/mol), both of which demonstrated promising favorable drug-likeness properties. Molecular dynamics simulation spanning 100 ns revealed structural stability of the identified leads. PCA and Gibbs free energy landscape study further corroborated the drug-candidacy of the leads. DFT-based molecular reactivity study unveiled Lupeol as the most kinetically stable compound (6.915 eV). The findings highlight the significance of multi-disciplinary approach integrating classical taxonomy with bioinformatics and pave the way for future colorectal cancer therapeutics. Bangladesh J. Plant Taxon. 31(2): 239-264, 2024 (December)